Safety and efficiency of procedural sedation and analgesia (PSA) conducted by medical officers in a level one hospital in Cape Town - Wenzel-Smith, Gisela (Department of Public Health and Family Medicine, 2015)
Objectives: This study aimed to research efficacy and safety of procedural sedation and analgesia (PSA) administered by medical officers (MOs), without formal anaesthetic training, in a South African district hospital. Design: This is a retrospective descriptive study. Setting: The study took place in the Emergency Department (ED) of False Bay Hospital (FBH), a level one hospital in the Southern suburbs of the Cape Town Metro health district.